San Marino : Selected Issues and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
This Selected Issues paper for San Marino reviews developments in the financial sector and provides an update of the financial sector regulation and supervision. While Sammarinese financial institutions accept foreign deposits and managed funds to a much larger extent than comparators in neighboring regions, there are no mutual funds or international bonds issued under San Marino law unlike the common practice in several international financial centers. There is considerable room to increase the flexibility and innovation needed to remain internationally competitive while maintaining the strengths and soundness of the financial system.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet